The Headmaster’s Strategies in Implementing Management Based on Schools in SMP Muhammadiyah 4 Gempol, Pasuruan - Saiful Hadi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
This study aims to find out and explore how does the headmaster implement it? what is the obstacle facing him? what strategy is done? This research uses four approaches that are pedagogies, sociological, juridical and psychological. The sources of the data are primary and secondary. The instruments are interviews, observation guides, check list observation, and documentation. The research techniques are data reduction techniques, data presentation, and conclusions. From the results of the research of school-based management in SMP Muhammadiyah 4 Gempol, it can be concluded: The headmaster has implemented school-based management but the implementation has not fully implement school-based management. The headmaster as a leader using School Based Management still needs improvement and improvement of teacher quality and good cooperation with school partners. Constraints faced a) Lack of educational facilities and infrastructure b) lack of teacher competency c) lack of parental support of learning process, d) lack of intensive and maximal socialization, e) lack of master of technology. Strategies undertaken in implementing school-based management ie a) doing relationship with relevant agencies to provide the facilities and the infrastructure b) improving teacher competence by involving teachers in trainings c) doing relationship with parents to improve the quality of education. The implications of this research is expected for the headmasters and teachers to always perform their duties and functions respectively each other. To the teachers of SMP Muhammadiyah 4 Gempol, to always strive to improve the professionalism of work for the quality of school education in particular and in general can be better. To the relevant agencies would pay attention to the development of each school. Keywords: Strategy, Leadership, Management